Determination of ATP and its metabolites in dietary energy supplements by capillary electrophoresis - Saliha Ebru Büyüktuncel (Universidade de São Paulo, 2023)
Abstract This study aimed to develop a simple and fast capillary electrophoresis (CE) method for the simultaneous determination of adenosine triphosphate (ATP) and its metabolites in dietary energy supplements. Reverse polarity separation mode for faster separation of the three strong negatively charged analytes and capillaries with a 25 µm inner diameter was employed. At -433 V/cm field strength at background electrolyte (BGE) consist with 0.1 M tris-HCl, 0.5 mM tetradecyltrimethylammonium chloride (TTAC) as positively charged surfactant and 0.3 mg/mL hydroxypropylmethylcellulose (HPMC) to reduce the electroosmotic flow (EOF), a complete separation of the three species were achieved in less than 15 minutes. The data acquisition was conducted at a wavelength of 254 nm. Three different commercialised dietary energy supplements were analysed.